Assessing stress, protective factors and psychological well-being among undergraduate nursing students. (September 2018) - He, Flora Xuhua; Turnbull, Bev; Kirshbaum, Marilynne N.; Phillips, Brian; Klainin-Yobas, Piyanee
Abstract: Objectives: This study sought to examine predictors of psychological well-being (PWB) among nursing students at an Australian regional university. The study postulated that: stress would have a negative effect on PWB; internal factors such as self-efficacy, resilience and mindfulness would have a positive effect on PWB and, external factors like social support would have a positive effect on PWB. Design: A cross sectional descriptive predictive model was used to test the study hypotheses. Setting and Participants: Convenience sampling was used to recruit participants at an Australian regional university with non-traditional nursing cohorts and where the curriculum is predominantly taught on-line. Methods: Six validated scales (The Perceived Stress Scale; General Self-Efficacy Scale; Connor Davidson Resilience Scale; Multi-Dimensional Scale of Perceived Social Support; Psychological Wellbeing Scale, Mindfulness Awareness Scale) and a demographic inventory were administered as an online survey. A multiple linear regression analysis was performed to assess the internal and external factors to predict the participants' PWB. Results: Of the 1760 invitations distributed, 657 responses were returned; however, because some were found to be significantly incomplete, 538 responses only were used for the data analysis. Demographics illustrated the characteristics of a non-traditional cohort that was female dominated. All three hypotheses were supported. An unexpected finding was that while it might be anticipated that non-traditional cohorts will have stronger coping skills due to life experiences, this should not be assumed. We found that our participants had higher stress scores and lower psychological wellbeing, compared to the younger groups (nursing or health allied) reported in previous studies. It was perhaps due to their difficulties in juggling responsibilities between study, work and family and the nature of studying externally online. Conclusions: This study represents only a snapshot in time but emphasises the need for specific curriculum preparation to promote positive coping strategies. In this way, new graduates may be better prepared to engage with complex, demanding and ever-changing work environments across the globe. Highlights: Nursing students across the world experience psychological stress. Stress had a significant negative effect on psychological wellbeing, internal factors such as self-efficacy. Internal factors such as self-efficacy, resilience and mindfulness had a positive effect on psychological wellbeing. External factors such as social support had a significant positive effect impact on psychological wellbeing. The older students had higher stress and lower psychological wellbeing, compared to younger groups reported in previous studies.